2023
DOI: 10.1136/rapm-2022-104282
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of injection pressure measurement at peripheral nerves using high-resolution 40 MHz ultrasound in an anesthetized porcine model

Abstract: BackgroundFluid injection pressure measurement is promoted as a marker of needle tip position that discriminates between tissue layers. However, clinical ultrasound has insufficient resolution to identify the exact position of the needle tip. Our primary objective was to use 40 MHz ultrasound in anesthetized pigs in order to precisely locate the tip of the needle and measure opening injection pressure in muscle, at epineurium and in subepineurium.MethodsWe surgically exposed the axillae of four anesthetized pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…This research has identified a wide range of forces and pressures that are measured in muscles when subjected to a gentle touch and the indentation of the epineurium. This variation in force can be attributed to the needle tip position and is consistent with the previous studies conducted on pigs [6] and soft embalmed cadavers [10,21]. However, the standard ultrasound technology used in medical procedures does not provide a sufficient resolution to accurately determine the needle tip's precise location.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This research has identified a wide range of forces and pressures that are measured in muscles when subjected to a gentle touch and the indentation of the epineurium. This variation in force can be attributed to the needle tip position and is consistent with the previous studies conducted on pigs [6] and soft embalmed cadavers [10,21]. However, the standard ultrasound technology used in medical procedures does not provide a sufficient resolution to accurately determine the needle tip's precise location.…”
Section: Discussionsupporting
confidence: 88%
“…However, this approach fails to account for the myriad of circumneural collagen fibres and fat cells [4] that reduce local anaesthetic delivery to the axons, according to Fick's law of diffusion [5]. Fat-filled circumneural fascial tissue is only visible via histology [4] or experimental 40 MHz microultrasound [6]. Accordingly, different authors [2,5,6] have recommended that the nerve is touched gently [6] so that the aperture of the block needle partially covers the epineurium and the injectate takes the path of least resistance away from the stiff epineurium to the elastic circumneural fat compartments [7].…”
Section: Introductionmentioning
confidence: 99%